Healthcare professionals’ experiences of discussing sexual function with menopausal women using a vaginal pessaryAJOG Global Reports at a Glance - Monica Quinlan, BSc, MSc; Victor Olagundoye, MBBS, MMedSci, MSc, MRCOG (AJOG Global Reports, 2025)
BACKGROUND: Pelvic organ prolapse is a common condition with high prevalence among postmenopausal women, many of whom are sexually active. A vaginal pessary is an effective, nonsurgical treatment alternative for well-selected, motivated patients and those unfit for surgical management. Open discussion on sexual function is a crucial part of counseling in these women to ensure that they are fitted with the most appropriate pessary and minimize complications. OBJECTIVE: This study aimed to explore healthcare professionals’ experiences of discussing sexual function with postmenopausal women with pelvic organ prolapse receiving vaginal pessary management in a urogynecology clinic. STUDY DESIGN: Semistructured, in-depth qualitative interviews were conducted in a tertiary university teaching hospital in England with an established urogynecology department. The sample comprised 10 volunteers (7 female and 3 male, consisting of 3 consultants, 1 advanced nurse practitioner, 2 clinical nurse specialists, and 4 specialist registrars). All volunteers were experienced in managing women with prolapse, including inserting and removing vaginal pessaries and discussing sexual intercourse and intimacy. RESULTS: Postmenopausal women were found to be reluctant and embarrassed to engage in open discussion on sexual intimacy, which can be improved by building trust. Being seen by female healthcare professionals, having a female chaperone, and using appropriate interpreters (in cases of language barriers) significantly improved women's willingness to discuss sexual issues. CONCLUSION: The study demonstrated that postmenopausal women found it difficult and were hesitant and embarrassed to openly discuss sexual issues, which is important in choosing the most suitable vaginal pessary. This problem can be alleviated by building trust between healthcare professionals and patients, by healthcare professionals remaining sensitive to patients’ ethnic and cultural backgrounds, and by respecting women's choice of healthcare professional.